2013
DOI: 10.1097/jto.0b013e31829f6b4a
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Type of Epidermal Growth Factor Receptor Mutations in Moroccan Patients with Lung Adenocarcinoma

Abstract: Some one fifth of lung AC tumors in Moroccan patients harbor EGFR mutations. This mutation frequency is higher than that found in whites but lower than in Asian population. Further studies, in larger numbers of patients, are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 15 publications
8
44
0
Order By: Relevance
“…[3][4][5] Of note, in our retrospective study that was recently published in this journal, the rate of rare EGFR mutations (exon 20 analysis was also performed) was 10% of all mutations. 6 Finally, we agree with the authors' statement with regard to the fact that some of their results need to be confirmed in a prospective setting because in any retrospective study, some sources of bias cannot be ruled out.…”
supporting
confidence: 76%
“…[3][4][5] Of note, in our retrospective study that was recently published in this journal, the rate of rare EGFR mutations (exon 20 analysis was also performed) was 10% of all mutations. 6 Finally, we agree with the authors' statement with regard to the fact that some of their results need to be confirmed in a prospective setting because in any retrospective study, some sources of bias cannot be ruled out.…”
supporting
confidence: 76%
“…Other studies from a single institution or country revealed a lower mutation rate, as in a recent study of 137 patients from Morocco, which reported a mutation rate of 20% (10). In another study on 106 Lebanese patients with adenocarcinoma, only 8.5% harbored EGFRmut (11).…”
Section: Discussionmentioning
confidence: 90%
“…A separate study showed EGFR mutation rate was 35% in the Asian race, while non-smoking adenocarcinoma mutation rate was 59%10. In the Monaco race11, lung adenocarcinoma mutation rate was 21% (28/137). In the present study, EGFR mutation rate was 55.4%.…”
Section: Discussionmentioning
confidence: 94%